2002
DOI: 10.1017/s0022029902005770
|View full text |Cite
|
Sign up to set email alerts
|

Addition of protected and unprotected fish oil to diets for dairy cows. I. Effects on the yield, composition and taste of milk

Abstract: Thirty Holstein cows in mid-lactation (158±20 DIM) were given a total mixed ration based on grass silage, maize silage and rolled barley. After a preliminary period of 1 week, this diet was supplemented with nothing (control), unprotected fish oil (3.7% of dry matter, DM), or two levels of glutaraldehyde-protected microcapsules of fish oil (1.5% and 3.0% of DM, respectively). Unprotected and protected supplements contained, respectively, 74% and 58% of DM as lipids. Cows given the unprotected supplement reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 8 publications
5
24
0
1
Order By: Relevance
“…With antioxidants, different in the water and lipid solubility supplied into the feed (into the rumen or the abomasum as into the milk) the milk flavour decreased quickly with the time after milking. Comparable results have been presented by Lacasse et al (1998).…”
supporting
confidence: 64%
“…With antioxidants, different in the water and lipid solubility supplied into the feed (into the rumen or the abomasum as into the milk) the milk flavour decreased quickly with the time after milking. Comparable results have been presented by Lacasse et al (1998).…”
supporting
confidence: 64%
“…The milk was produced by feeding cows with supplementary soybean oil and fish oil. Lacasse, Kennelly, Delbecchi, and Ahnadi (2002), in contrast, reported that a taste panel easily detected deterioration of pasteurized and homogenized milk from cows fed protected (3%) and unprotected (3.7%) fish oil. However, the supplementation of fish oil in their study was rather high compared with other studies.…”
Section: Technological Effectsmentioning
confidence: 97%
“…Supplementation with DHA and EPA from fish oil did not affect rumen environment nor fiber digestion [11] but may affect the palatability of the animal ration as well as the taste, smell and rancidity of the final dairy products [12]. This can be prevented by using other organisms of marine origin such as algae and plankton that are rich in EPA and DHA [13] and also heterotrophic microalgae such as Schizochytrium limacinum (All-G-Rich, Alltech Inc.).…”
Section: Introductionmentioning
confidence: 99%